Effects of low sodium diet versus high sodium diet on blood pressure, renin, aldosterone, catecholamines, cholesterol, and triglyceride - Graudal, Niels Albert; Hubeck-Graudal, Thorbjorn; Jurgens, Gesche (Cochrane database of systematic reviews, 2011)
In spite of more than 100 years of investigations the question of reduced sodium intake as a health prophylaxis initiative is still unsolved. To estimate the effects of low sodium versus high sodium intake on systolic and diastolic blood pressure (SBP and DBP), plasma or serum levels of renin, aldosterone, catecholamines, cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL) and triglycerides. PUBMED, EMBASE and Cochrane Central and reference lists of relevant articles were searched from 1950 to July 2011. Studies randomizing persons to low sodium and high sodium diets were included if they evaluated at least one of the above outcome parameters. Two authors independently collected data, which were analysed with Review Manager 5.1. A total of 167 studies were included in this 2011 update.The effect of sodium reduction in normotensive Caucasians was SBP -1.27 mmHg (95% CI: -1.88, -0.66; p=0.0001), DBP -0.05 mmHg (95% CI: -0.51, 0.42; p=0.85). The effect of sodium reduction in normotensive Blacks was SBP -4.02 mmHg (95% CI:-7.37, -0.68; p=0.002), DBP -2.01 mmHg (95% CI:-4.37, 0.35; p=0.09). The effect of sodium reduction in normotensive Asians was SBP -1.27 mmHg (95% CI: -3.07, 0.54; p=0.17), DBP -1.68 mmHg (95% CI:-3.29, -0.06; p=0.04). The effect of sodium reduction in hypertensive Caucasians was SBP -5.48 mmHg (95% CI: -6.53, -4.43; p<0.00001), DBP -2.75 mmHg (95% CI: -3.34, -2.17; p<0.00001). The effect of sodium reduction in hypertensive Blacks was SBP -6.44 mmHg (95% CI:-8.85, -4.03; p=0.00001), DBP -2.40 mmHg (95% CI:-4.68, -0.12; p=0.04). The effect of sodium reduction in hypertensive Asians was SBP -10.21 mmHg (95% CI:-16.98, -3.44; p=0.003), DBP -2.60 mmHg (95% CI: -4.03, -1.16; p=0.0004).In plasma or serum there was a significant increase in renin (p<0.00001), aldosterone (p<0.00001), noradrenaline (p<0.00001), adrenaline (p<0.0002), cholesterol (p<0.001) and triglyceride (p<0.0008) with low sodium intake as compared with high sodium intake. In general the results were similar in studies with a duration of at least 2 weeks. Sodium reduction resulted in a 1% decrease in blood pressure in normotensives, a 3.5% decrease in hypertensives, a significant increase in plasma renin, plasma aldosterone, plasma adrenaline and plasma noradrenaline, a 2.5% increase in cholesterol, and a 7% increase in triglyceride. In general, these effects were stable in studies lasting for 2 weeks or more.